2007
DOI: 10.1007/s00404-007-0390-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-hormonal therapy of post-menopausal vasomotor symptoms: a structured evidence-based review

Abstract: There is evidence that clonidine, paroxetine, venlafaxine, gabapentin and black cohosh may be beneficial in the treatment of menopausal vasomotor symptoms in some women. Current evidence does not support the use of fluoxetine, red clover, phytoestrogens, Ginseng, evening primrose, dong quai and vitamin E. The side effects profile of these therapies should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 65 publications
0
41
0
8
Order By: Relevance
“…It has been suggested that central NE/5-HT equilibrium can have a stimulatory or inhibitory effect on the eccrine sweat glands, depending on the resulting NE tone [11] . Consistent with this hypothesis, drugs with significant NE and 5-HT reuptake inhibition -like paroxetine, venlafaxine and tricyclic antidepressants -show improvement in postmenopausal hot flushes and sweating, but not others like fluoxetine with no significant NE reuptake properties [12,13] . Also, mirtazapine with both NE and 5-HT action has been found useful in hyperhidrosis [14] .…”
Section: Discussionmentioning
confidence: 55%
“…It has been suggested that central NE/5-HT equilibrium can have a stimulatory or inhibitory effect on the eccrine sweat glands, depending on the resulting NE tone [11] . Consistent with this hypothesis, drugs with significant NE and 5-HT reuptake inhibition -like paroxetine, venlafaxine and tricyclic antidepressants -show improvement in postmenopausal hot flushes and sweating, but not others like fluoxetine with no significant NE reuptake properties [12,13] . Also, mirtazapine with both NE and 5-HT action has been found useful in hyperhidrosis [14] .…”
Section: Discussionmentioning
confidence: 55%
“…a 4 b 2 g 2S ). Due to the positive GABA A allosteric modulatory effects of Ac-SM (and potentially other cycloartane glycosides; Cicek et al, 2010), it is tempting to speculate that this GABA A receptor modulation leading to sedation and muscle relaxation contributes to the alleviation of mild to moderate symptoms in menopause reported in clinical studies with preparations from A. racemosa L., especially when hot flushes are associated with sleep and mood disturbances Frei-Kleiner et al, 2005;Osmers et al, 2005;Verhoeven et al, 2005;Newton et al, 2006;Pockaj et al, 2006;Uebelhack et al, 2006;Cheema et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Skuteczność akupunktury w leczeniu uderzeń gorąca określa się na ok. 50%, więc nie jest to leczenie tak skuteczne jak MHT, ale dużą zaletą tej metody jest to, że można ją stosować również u pacjentek z nowotworem piersi [50,[57][58][59]. Obecnie w wielu ośrodkach, szczególnie tam, gdzie znalazły zastosowanie zasady medycyny integracyjnej, akupunktura jest stosowana jako jedna z metod terapii, w tym leczenia uderzeń gorąca [60][61][62][63][64][65][66].…”
Section: Wstępunclassified